A refined protocol for the isolation and monoculture of primary mouse renal peritubular endothelial cells - Thompson, Austin D.; Janda, Jaroslav; Schnellmann, Rick G. (Frontiers in Cardiovascular Medicine, 2023)
During an episode of acute kidney injury (AKI), a sudden and rapid decline in renal function is often accompanied by a persistent reduction in mitochondrial function, microvasculature dysfunction/rarefaction, and tubular epithelial injury/necrosis. Additionally, patients who have experienced an AKI are at an elevated risk of developing other progressive renal, cardiovascular, and cardiorenal related diseases. While restoration of the microvasculature is imperative for oxygen and nutrient delivery/transport during proper renal repair processes, the mechanism(s) by which neovascularization and/or inhibition of microvascular dysfunction improves renal recovery remain understudied. Interestingly, pharmacological stimulation of mitochondrial biogenesis (MB) post-AKI has been shown to restore mitochondrial and renal function in mice. Thus, targeting MB pathways in microvasculature endothelial cell (MV-EC) may provide a novel strategy to improve renal vascular function and repair processes post-AKI. However, limitations to studying such mechanisms include a lack of commercially available primary renal peritubular MV-ECs, the variability in both purity and outgrowth of primary renal MV-EC in monoculture, the tendency of primary renal MV-ECs to undergo phenotypic loss in primary monoculture, and a limited quantity of published protocols to obtain primary renal peritubular MV-ECs. Thus, we focused on refining the isolation and phenotypic retention of mouse renal peritubular endothelial cells (MRPEC) for future physiological and pharmacological based studies. Here, we present a refined isolation method that augments the purity, outgrowth, and phenotypic retention of primary MRPEC monocultures by utilizing a collagenase type I enzymatic digestion, CD326+ (EPCAM) magnetic microbead epithelial cell depletion, and two CD146+ (MCAM) magnetic microbead purification cycles to achieve a monoculture MRPEC purity of ≅ 91–99% by all markers evaluated.